Functional soil microbes drive soil phosphorus fractions in response to nitrogen addition across aggregate levels - Hu, Jiaxin; Cui, Haiying; Fan, Mingcai; Liu, Min; Wang, Shanling; Li, Xiuping; Peng, Xia; Shi, Fengxue; Song, Wenzheng; Sun, Wei (Frontiers in Microbiology, 2025)
Phosphorus (P) is one of the most important limiting nutrients for plant productivity in terrestrial ecosystems. As key drivers of P cycling processes, changes in soil microbial diversity and community structure can influence soil P cycling and availability. Nitrogen (N) deposition, as a global change factor, profoundly alters soil P cycling; yet how soil P fractions respond to N addition across multiple gradients, and the potential mechanisms driven by plant, microbial, and soil properties at the soil aggregate level, remains unclear. In this study, we conducted a seven-year, long-term field experiment to investigate the response patterns of soil labile and non-labile P fractions to N addition at the four gradient levels (0, 5, 10, and 20 g N m−2 y−1) in macroaggregates and microaggregates in a meadow steppe in Northeast China. We found that N addition reduced the content of soil non-labile P in macroaggregates, but increased all P fractions in microaggregates. Soil functional microbes play different roles in driving soil P fractions. Soil labile and non-labile P fractions were mainly controlled by the diversity and gene abundance of soil phoD-harboring bacteria, and plant and soil properties in macroaggregates, but by soil microbial stoichiometry in microaggregates. Moreover, N addition indirectly regulated P fractions by altering microbial functional traits, rather than directly by the changes of soil nutrient availability. Our results demonstrate that the mechanisms by which soil functional microbes and microbial stoichiometry regulate soil P fractions and transformation vary among soil aggregates. This study provides new insights into the crucial role of soil functional microbes in improving P supply by accelerating the process of soil P fractions under global change scenarios. To enhance sustainable grassland development in the changing world, we need to prioritize the leveraging of soil aggregate-mediated processes in grasslands.